2009
DOI: 10.1128/jvi.00386-09
|View full text |Cite
|
Sign up to set email alerts
|

The M33 Chemokine Receptor Homolog of Murine Cytomegalovirus Exhibits a Differential Tissue-Specific Role during In Vivo Replication and Latency

Abstract: M33, encoded by murine cytomegalovirus (MCMV), is a member of the UL33 homolog G-protein-coupled receptor (GPCR) family and is conserved across all the betaherpesviruses. Infection of mice with recombinant viruses lacking M33 or containing specific signaling domain mutations in M33 results in significantly diminished MCMV infection of the salivary glands. To determine the role of M33 in viral dissemination and/or infection in other tissues, viral infection with wild-type K181 virus and an M33 mutant virus, ⌬M3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
94
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(109 citation statements)
references
References 74 publications
9
94
0
1
Order By: Relevance
“…This phenotype was associated with a lower DNA viral load in both organs and with a lower number of infected cells in the spleen. It also showed that M33 G protein signalling was involved with reactivation in both organs, as signalling mutant viruses (R131Q) present a reduced reactivation rate (Cardin et al, 2009;Farrell et al, 2011). Taken together, these data suggest that the vGPCR could play a part in colonization and/or replication of specific cell types during viral dissemination.…”
Section: Introductionmentioning
confidence: 54%
See 4 more Smart Citations
“…This phenotype was associated with a lower DNA viral load in both organs and with a lower number of infected cells in the spleen. It also showed that M33 G protein signalling was involved with reactivation in both organs, as signalling mutant viruses (R131Q) present a reduced reactivation rate (Cardin et al, 2009;Farrell et al, 2011). Taken together, these data suggest that the vGPCR could play a part in colonization and/or replication of specific cell types during viral dissemination.…”
Section: Introductionmentioning
confidence: 54%
“…Although not tested here, previous reports (Cardin et al, 2009) showed that M33 was attenuated in spread to the spleen following i.n. infection, demonstrating a M33-dependent defect in virus colonisation beyond the viraemic phase of infection.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations